2019
DOI: 10.1038/s41409-019-0478-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of autologous stem cell transplantation in patients aged ≥ 65 years with multiple myeloma in the era of novel agents

Abstract: Clinical trials evaluating the role of autologous hematopoietic stem cell transplantation (auto-HCT) in multiple myeloma have mostly included patients aged <65 years. Therefore, this study was aimed to evaluate the efficacy and safety of auto-HCT in elderly patients with multiple myeloma in the era of novel agents. We retrospectively analyzed 2056 patients with multiple myeloma, who underwent auto-HCT in 2007-2014 (287 were aged ≥65 years). We evaluated the 100-day treatment-related mortality (TRM) and overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Moreover, data from both groups suggest that selected elderly patients receiving ASCT have similar outcome to those of younger patients. Similar results have been more recently confirmed from Japanese registry data 26 . Furthermore, the advent of novel agents may have contributed to improve outcomes, allowing a higher number of patients to undergo ASCT in better clinical conditions and with a lower disease burden 27 .…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Moreover, data from both groups suggest that selected elderly patients receiving ASCT have similar outcome to those of younger patients. Similar results have been more recently confirmed from Japanese registry data 26 . Furthermore, the advent of novel agents may have contributed to improve outcomes, allowing a higher number of patients to undergo ASCT in better clinical conditions and with a lower disease burden 27 .…”
Section: Discussionsupporting
confidence: 69%
“…Similar results have been more recently confirmed from Japanese registry data. 26 Furthermore, the advent of novel agents may have contributed to improve outcomes, allowing a higher number of patients to undergo ASCT in better clinical conditions and with a lower disease burden. 27 The role of ASCT in older adults MM patients have been investigated by several retrospective single center studies.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, transplant outcomes of multiple myeloma have been improving by combining novel agents (NA), second-generation proteasome inhibitors, third-generation immunomodulators, and antibody drugs with induction therapy 22 . In fact, despite being a common disease in older patients, some reports from Europe and Japan, where aging is progressing, showed that autologous transplants for MM in that population were safe and effective 23,24 . Thus, the number of autologous transplants for MM is expected to increase in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding overall survival (OS) , comparing the non-elderly group with the elderly group after five years of median follow-up, we found a higher rate of OS in patients younger than 65 years (58.2% [95%CI, 54.2-62.1%]) when compared to those older than 65 years (42.6% [95%CI, 31.6-53.2%]). 2 It was also shown that after three years, there was a higher OS in the 18 to 59-year-old group (78% [95%CI, 76-79]) when compared to the patients aged 70 years and older (72% [95%CI, 67-76]). 3 When it comes to progression-free survival (PFS) , there was no significant difference between the elderly and non-elderly.…”
Section: Methodsmentioning
confidence: 95%